(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
One of the most influential aspects in determining the degree of satisfaction with the bankingindustry is the nature of the connection between the customer and the provider of the products andservices given by banks. This study investigates the relationship between client happiness and loyalty inthe Indian banking industry and analyzes the degrees of consumer happiness and loyalty between privatesector and public sector banks in India. A sufficient sample size of 650 respondents was recruited fromboth private and public sector banks in Chennai for the purpose of the study. For the purpose of the study,statistical methods such as percentage analysis, the t-test, factor analysis, and cluster analysis wereutilised. The findings of the study indicate that banks in both the private and public sectors need toadhere to the highest possible standards of service quality, which can have a positive sequential impacton the degree to which customers are satisfied and loyal to the institution.